Distribusi Spasial Kasus Kecacingan (Ascaris lumbricoides) Terhadap Personal Higiene Anak Balita di Pulau Kodingareng Kecamatan Ujung Tanah Kota Makassar Tahun 2016 - Andi Tri Rezki Amaliah; Azriful Azriful (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
The worms infection is one of the disease that is very general, which is spread and contagious a lot of people in the world. Until now, this deaseas is still being a polemic because of the social condition and the economic condition in several place in the world. The worms phenomenon has the connectivity with the human’s characteristic, the environment, and the time. Kodingareng Lompo Island is the one of the island that placed in Makassar that become the highest victim area of the worms disease. So that, this research has the purpose to find out the spatial distribution of the wroms phenomenon in Kodingareng Lompo Island, Subdistrict Ujung Tanah Makassar City 2016. The sort of this research, is the quantitative research that using observational descriptive planning. The population in this research is all the worms disease case in 2016 and the sample is taken by using total sampling, with aggregate the 121 respondent.The researcher do the investigation for feces 121 respondent in laboratorium and find out the result that there are 73 respondents have the  possitive   get attacked by worms diseas and 48 with negative result of the worms diseas. The mapping by  using Global Positioning System (GPS).The result of this research indicates that most of using sandals/shoes is 31,5%, nail sanitation protection category is 21,9%, the hand protection category is 9.6%, playing on the ground category is 76,7%, clothes sanition protection category is 15,1% , teeth sanition protection category  is 21,3%,the most always showering behavior category is once a day is 74,0%. The worst of personal hygine and environmental sanitation that the lack of adequate become a problem that related to the worms illness in Kodingareng Lompo Island.Suggested the socialization to the people about the worms disease, through the print media  or make the informal gathering and make an effort to increase the environment quality and personl hygine to avoid distributing the worms illness such as, toilet equipping, sewer water waste and the trash supplying. Key word : Worms, Ascaris lumbricoides, spatial distribution